2-(1,2,4-triazole-5-yl)-1,3,4-oxadiazole as a novel building block for energetic materials - Dong, Zheting; Wu, Zhengqiang; Zhang, Qiang; Xu, Yuangang; Lu, Guo-Ping (Frontiers in Chemistry, 2022)
The exploration of novel nitrogen-rich heterocyclic building blocks is of importance in the field of energetic materials. A series of 2-(1,2,4-triazole-5-yl)-1,3,4-oxadiazole derivatives based on a new energetic skeleton have been first synthesized by a simple synthetic strategy. All three compounds are well-characterized by IR spectroscopy, NMR spectroscopy and thermal analysis. The compounds 5 and 8 are further characterized by single-crystal X-ray diffraction analysis. 8 and its salts (8a-8c) possess relative high decomposition temperature and low sensitivity, while 5 exhibits low decomposition temperature and high sensitivity. According to EXPLO5 calculation results of detonation performance, both 5 and 8 display acceptable detonation velocities (D) of 8450 m/s and 8130 m/s and detonation pressures (P) of 31.6 GPa and 29.2 GPa, respectively. Furthermore, 5 containing a rare diazonium ylide structure shows high impact sensitivity (4.5 J), making it has a potential as a primary explosive.